2020
DOI: 10.1126/sciadv.abc6389
|View full text |Cite
|
Sign up to set email alerts
|

Artificial visual systems enabled by quasi–two-dimensional electron gases in oxide superlattice nanowires

Abstract: Rapid development of artificial intelligence techniques ignites the emerging demand on accurate perception and understanding of optical signals from external environments via brain-like visual systems. Here, enabled by quasi–two-dimensional electron gases (quasi-2DEGs) in InGaO3(ZnO)3 superlattice nanowires (NWs), an artificial visual system was built to mimic the human ones. This system is based on an unreported device concept combining coexistence of oxygen adsorption-desorption kinetics on NW surface and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 79 publications
0
70
0
Order By: Relevance
“…[50] In these cases, the interaction of simultaneous light pulses with adsorbed and bulk oxygen in the surface depletion region play a key role in regulating the NW conductance, that is, the synaptic weight. [9,51] In a recent work, both volatile and non-volatile resistive switching have been achieved in Ag-contacted ZnO nanowire devices, mainly enabled by the atomic Ag diffusion along the NW (Figure 2f,g), which well emulate the ion migration dynamics in biological synapses. [35] With detailed investigation of the memristive mechanism in the Ag-ZnO system, the underlying electrochemical fundamentals of filament formation/dissolution highlight the Ag + /Ag redox reactions and transport characteristics on the crystalline NW surface.…”
Section: D Quantum Materials For Artificial Synapsesmentioning
confidence: 90%
See 4 more Smart Citations
“…[50] In these cases, the interaction of simultaneous light pulses with adsorbed and bulk oxygen in the surface depletion region play a key role in regulating the NW conductance, that is, the synaptic weight. [9,51] In a recent work, both volatile and non-volatile resistive switching have been achieved in Ag-contacted ZnO nanowire devices, mainly enabled by the atomic Ag diffusion along the NW (Figure 2f,g), which well emulate the ion migration dynamics in biological synapses. [35] With detailed investigation of the memristive mechanism in the Ag-ZnO system, the underlying electrochemical fundamentals of filament formation/dissolution highlight the Ag + /Ag redox reactions and transport characteristics on the crystalline NW surface.…”
Section: D Quantum Materials For Artificial Synapsesmentioning
confidence: 90%
“…[90] Given high carrier mobility together with high sensitivity to various stimuli, quasi-2DEGs systems may enable more accurate probing of complex biological dynamics than that can be achieved by other material systems. [9,91] Lately, Dror Miron et al demonstrated a non-volatile resistive switching device based on quasi-2DEGs established between the SrTiO 3 substrate and the amorphous Al 2 O 3 layer. [88] The oxygen vacancies from the SrTiO 3 /Al 2 O 3 conductive interface could drift into (out of) the Al 2 O 3 layer under negative (positive) bias, leading to the formation (breakage) of the conductive filament.…”
Section: Quasi-2d Electron Gases Interfaces For Artificial Synapsesmentioning
confidence: 99%
See 3 more Smart Citations